PEMBERDAYAAN MASYARAKAT SEBAGAI UPAYA MEMBANGUN KETAHANAN SOSIAL DI JAKARTA UTARA: : Studi Kasus Kampung Aquarium Tanah Merah - moch. Arfan Rifa'i (Institut Pemerintahan Dalam Negeri, 2025)
This research examines community empowerment as a strategy to build social resilience in North Jakarta, specifically in Kampung Aquarium and Kampung Tanah Merah, during the leadership of Governor Anies Baswedan. Employing a qualitative descriptive method with literature study and relevant field documentation, the findings reveal that the Kampung Susun Aquarium program and the administrative legalization of Tanah Merah are progressive policies rooted in community participation. Through a collaborative approach involving local government, grassroots communities, and civil society organizations, a model of empowerment emerged that prioritizes the right to the city and social justice. Kampung Susun provides not only adequate housing but also revives social, economic, and cultural networks previously dismantled by forced evictions. Similarly, the partial legalization of Tanah Merah has enabled access to public services and civil documents. Nonetheless, challenges persist, including the absence of permanent land tenure, limited infrastructure, and reliance on inconsistent political will. Therefore, regulatory strengthening, human resource capacity building, and policy continuity across administrations are essential to ensure long-term success. This study concludes that social resilience can be achieved through inclusive and sustainable empowerment, provided there is strong political commitment and active community involvement throughout the planning and evaluation stages of urban development